ANALISIS PENETAPAN SANKSI TERHADAP ANAK SEBAGAI PELAKU JARIMAH BERDASARKAN QANUN NOMOR 6 TAHUN 2014 TENTANG HUKUM JINAYAT DAN MAQASHID SYARIAH (STUDI PUTUSAN NOMOR: 01/JN.ANAK/2020/MS.TKN) - Mauliza, Isna; Faisal, Faisal; Hamdani, Hamdani (Fakultas Hukum Universitas Malikussaleh, 2023)
This study aims to examine the analysis of the judge's considerations in deciding the decision in case Number: 01/JN.Anak/2020/MS.Tkn based on Qanun Number 6 of 2014 concerning Jinayat Law and maqashid sharia. This research uses qualitative research with a normative legal research approach or what is usually called library research. Based on the research results, it is known that in deciding and considering the case with Decision Number: /JN.Anak/2020/MS.Tkn, the author does not agree with the judge's decision to consider this case a case of sexual harassment because of the facts revealed in The trial of this case could be classified as a rape case. In the view of maqashid syari'ah itself, the perpetrator's actions in this case can be concluded to be contrary to the 5 (five) main points of benefit to be achieved in maqashid syari'ah, namely hifz ad-din, hifz 'aql, hifz nasl, hifz maal, and hifz nafs.